Perancangan Aplikasi Kompresi File Video Menggunakan Algritma SPIHT (Set Partioning In Hirarcical Tress) - Rita Megawati Siburian; Mesran; Henry K Siburian (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Video files have a large enough capacity, and to access them takes a long time, so a data compression technique is needed. In this case the video file will be compressed using the SPIHT (Set Partitioning In Hierarchical Trees) algorithm, SPIHT (Set Partitioning In Hierarchical Trees) is a video file compression capable of achieving a high compression ratio. Problems that arise due to the large file size include the wasteful storage media used, as well as more time in terms of data exchange, data transfer over the internet is a big problem in Indonesia because of the very low download and upload speeds. To overcome this problem, data compression techniques are needed. The concept of compression was born as a real solution to problems regarding the space needed to store various digital files, including the MKV (Matroska Video) format video files. The compression technique is a technique that compresses files so that they become smaller in size while maintaining the quality of the representation of the file. Through the compression process of MKV (Matroska video) format video files using the SPIHT (Set Partioning In Hirarcical Tress) algorithm, it is hoped that in the future this compression system will have a major effect on video file storage and can increase storage and it is also hoped that this algorithm can be used for other objects to be compressed.